Internet of Things-Driven Information Sharing: A Strategic Approach to Mitigating Supply Chain Risks - Al Kurdi, Barween; Alzoubi, Haitham M.; Tan, Cheng Ling; El Khatib, Mounir; Yanamandra, Ramakrishna; Ozturk, Ilknur; Shwedeh, Fanar (International Review of Management and Marketing, 2025)
This research explores the integration of the Internet of Things (IoT) in mitigating supply chain risks within the retail industry, highlighting the crucial role of information sharing strategies as a mediating factor. Through an extensive analysis, the study reveals that all examined relationships between IoT implementation, supply chain risk mitigation, and the effectiveness of information sharing are positively correlated and statistically significant, suggesting that enhanced IoT capabilities can lead to more effective risk management through improved data transparency and communication among stakeholders. A key limitation of this research is the reliance on quantitative data, which may not fully capture the nuanced experiences of industry practitioners; future studies could benefit from qualitative insights to deepen understanding. Practically, this research underscores the necessity for hospitality organizations to develop robust information sharing strategies that leverage IoT technologies, ultimately fostering resilience and adaptability in supply chains. Additionally, this study contributes to the hospitality sector by providing a framework that integrates modern technological solutions with strategic management practices, guiding industry leaders in enhancing operational efficiency and customer satisfaction through proactive risk management.